Long-term outcomes and prognostic factors for survival of patients with ANCA-associated vasculitis - Sánchez Álamo, Beatriz; Moi, Laura; Bajema, Ingeborg; Faurschou, Mikkel; Flossmann, Oliver; Hauser, Thomas; Hruskova, Zdenka; Jayne, David; Luqmani, Raashid; Mahr, Alfred; Åkesson, Anna; Westman, Kerstin (Nephrology, dialysis, transplantation, 2023)
BACKGROUND: Despite newer treatments with immunosuppressive agents, there still exists a considerable morbidity and mortality risk among patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Since 1994 the European Vasculitis Society (EUVAS) has aimed for an improved outcome for patients with AAV, conducting several prospective randomized controlled trials (RCTs). The aim for the present study was to further evaluate the long-term survival of patients with AAV included in seven RCTs conducted by the EUVAS as well as to identify potential prognostic factors. METHODS: Long-term follow-up data were collected from questionnaires sent to the principal investigators of the original RCTs (1995-2012): MEPEX, NORAM, CYCAZAREM, CYCLOPS, IMPROVE, RITUXVAS and MYCYC, comprising 848 patients, all newly diagnosed with AAV. Relative survival estimates are presented for the study cohorts. Demographic, clinical and laboratory characteristics at trial entry were studied as potential prognostic factors in multivariable models. RESULTS: A total of 478 (56%) patients had granulomatosis with polyangiitis (GPA) and 370 (44%) had microscopic polyangiitis (MPA) with a mean age at diagnosis of 58 ± 14 years. The median follow-up time was 8 years (interquartile range 2.9-13.6). During the observation period there were 305 deaths and the main causes were infections (26%), cardiovascular disease (14%) and malignancies (13%). When compared with a matched cohort (regarding country, age group and sex) from the background population there were 14.2% more deaths among our cohort of AAV patients at 5 years, 19.9% at 10 years, 28.8% at 15 years and 36.3% at 20 years. The excess mortality occurred in all age groups. The estimated median survival time (from diagnosis) was 17.8 years (95% confidence interval 15.7-20). Among variables measured at baseline, advanced age, male sex, low estimated glomerular filtration rate and low platelet count were identified as predictors of death in a multivariate Cox model. CONCLUSIONS: Patients with AAV still have an increased risk of mortality compared with the general population despite newer therapeutic regimens. Treatment complications and organ damage are the main causes of limited survival and infections remain the leading cause of mortality among patients with AAV.
Keywords: dospělí; předškolní dítě; Adult; ANCA-asociované vaskulitidy; granulomatóza s polyangiitidou; lidé; mikroskopická polyangiitida; Granulomatosis with Polyangiitis; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; prognóza; Antibodies, Antineutrophil Cytoplasmic; Male; Aged; Child, Preschool; Microscopic Polyangiitis; Prognosis; lidé středního věku; protilátky proti cytoplazmě neutrofilů; senioři; mužské pohlaví; Middle Aged; Humans